Effect of Hypothermic Storage in Various Media on Viability and Metabolic Activity of Human Mesenchymal Stromal Cells in Alginate Microspheres - Tarusin, Dmitriy N.; Zaikov, Vedeney S.; Mutsenko, Vitaliy V.; Petrenko, Yuriy A. (Problems of Cryobiology and Cryomedicine, 2015)
N/A